Study Of Biological Activity And Safety Of Phytocomposition Of Antidiabetol - Z.T, Fayzieva; O.M, Ibragimov; Islomova S, Islomova S; B.J, Azimova (Journal of Neonatal Surgery, 2025)
Objective: Modern lifestyles often lead to an imbalance between energy intake and expenditure, contributing to obesity, which is a major risk factor for type II diabetes. The consumption of unhealthy foods, high in refined sugars and unhealthy fats, leads to insulin resistance, where the body's cells do not respond effectively to insulin. Methods: The acute toxicity, allergenic, diuresis, immune system, hypoglycemic effect, course of experimental alloxan diabetes of the Antidiabetol capsule. In diabetes, the influence of Antidiabetol on the immune system and on diuresis plays a significant role. The study of the impact of Antidiabetol on the immune system was conducted using the Jerne and Nordin method, while the effect on diuresis was studied using the method of V.V. Gatsura. Results: This resistance is a precursor to type II diabetes. Additionally, chronic stress can impact hormone levels and metabolism, further exacerbating the risk of developing diabetes. Stress often leads to poor dietary choices and reduced physical activity, creating a cycle that contributes to weight gain and insulin resistance. Harmful habits, such as smoking and excessive alcohol consumption, also play a role in the development of diabetes. These behaviors can damage the body's systems and contribute to metabolic dysfunction. Conclusion: The study is concluded to investigate the safety and hypoglycemic activity of the “Antidiabetol” capsule.